1996
DOI: 10.1897/1551-5028(1996)015<0150:toawlt>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Aspen Wood Leachate to Aquatic Life: Laboratory Studies

Abstract: Abstract-Trembling aspen (Populus tremuloides Michx.), a common hardwood tree throughout Canada, is being harvested at increasing rates for use in paper and building materials. Piles of aspen logs have been observed to produce a dark, watery, acutely toxic leachate. A laboratory study was undertaken to elucidate the nature, strength, and persistence of aspen leachate toxicity and the chemical composition of the leachate. Leaching from aspen chips in the laboratory was rapid, with 1% mass loss in the first 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 0 publications
1
30
1
Order By: Relevance
“…However, if such materials were to be discharged into rivers, lakes, and estuaries at excessive levels, the resulting biological metabolism would sometimes be sufficient to consume all or most of the available dissolved oxygen, leading to the death of fish and other aquatic life (Taylor et al 1996;Chhonkar et al 2000). Such impacts are often quantified by measuring the BOD.…”
Section: Oxygen Demandmentioning
confidence: 99%
“…However, if such materials were to be discharged into rivers, lakes, and estuaries at excessive levels, the resulting biological metabolism would sometimes be sufficient to consume all or most of the available dissolved oxygen, leading to the death of fish and other aquatic life (Taylor et al 1996;Chhonkar et al 2000). Such impacts are often quantified by measuring the BOD.…”
Section: Oxygen Demandmentioning
confidence: 99%
“…This waste has the potential of creating large amounts of leachate containing solubilized compounds from decaying aspen bark, wood and leaves. Leachate generated from decked aspen logs and waste bark and wood is toxic to aquatic organisms (Goudey and Taylor 1992, Taylor 1994, Taylor et al 1996; aqueous extracts of P. tremuloides leaves decreased the growth of several grass species (Younger et al 1980); tissue culture extracts of P. tremuloides demonstrated antimicrobial activity (Mathes 1963) while leaf extracts of a closely related species, P. tremula, showed anti-fungal properties (Olsen et al 1971). …”
Section: Introductionmentioning
confidence: 99%
“…Those authors observed that higher toxic effects on the early stages of the runoff were gradually reduced, and that 90% of toxic effects were associated with the first 20% of the total runoff volume. Even though the toxic effects posed by wood-related compounds have been demonstrated [9,10,11,6,4], little is know concerning the intra-storm magnitude, variability and possible existence of toxic first flushes from stormwater runoff generated in log-yards. The aim of this paper was to evaluate the magnitude and the intra-storm variability of the toxic effects posed by stormwater runoff originated from a log-yard during single storm events.…”
Section: Introductionmentioning
confidence: 99%